2003
DOI: 10.1074/jbc.m308889200
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated HuR Depletion Leads to the Inhibition of Muscle Cell Differentiation

Abstract: The formation of muscle fibers involves the sequential expression of many proteins that regulate key steps during myoblast-to-myotube transition. MyoD, myogenin, and the cyclin-dependent kinase inhibitor p21 cip1 are major players in the initiation and maintenance of the differentiated state of mouse embryonic muscle cells (C2C12). The messenger RNAs encoding these three proteins contain typical AU-rich elements (AREs) in their 3-untranslated regions (3-UTRs), which are known to affect the half-life of many sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
185
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(198 citation statements)
references
References 59 publications
13
185
0
Order By: Relevance
“…We and others have shown that stabilization of inherently labile muscle specific transcripts takes place during C2C12 cell differentiation. [6][7][8] Myogenin and p21 mRNAs are unstable in C2C12 myoblasts cultured in GM and KSRP is required for their decay while MAPK p38-induced inactivation of KSRP (which occurs in differentiating myoblasts) contributes to myogenin and p21 induction. 8 Figure 5a and Supplementary Figure S6a show that AKT increased the half life of myogenin and p21 mRNAs when activated in C2C12 myoblasts cultured in GM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that stabilization of inherently labile muscle specific transcripts takes place during C2C12 cell differentiation. [6][7][8] Myogenin and p21 mRNAs are unstable in C2C12 myoblasts cultured in GM and KSRP is required for their decay while MAPK p38-induced inactivation of KSRP (which occurs in differentiating myoblasts) contributes to myogenin and p21 induction. 8 Figure 5a and Supplementary Figure S6a show that AKT increased the half life of myogenin and p21 mRNAs when activated in C2C12 myoblasts cultured in GM.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the recent few years, extensive analysis of the composition of the transcriptome assembled on the chromatin of myogenic loci has been performed (reviewed in Guasconi and Puri 5 ), although knowledge on the mechanisms that post-transcriptionally regulate muscle differentiation and regeneration is more limited. [6][7][8][9] Recently, genetic, and biological evidence of an essential role of microRNAs (miRNAs) in muscle development and function has been accumulating and a group of miRNAs, highly enriched in skeletal muscle (referred to as myomiRs), has been identified (reviewed in Williams et al, 10 and Gü ller and Russell 11 ). MyomiRs influence multiple aspects of muscle development and function through their regulation of key genes controlling myogenesis.…”
mentioning
confidence: 99%
“…[37][38][39] Published reports from our lab and others demonstrate that HuR critically regulates myogenesis by controlling the expression of three central genes in this process. 40,41 HuR siRNA knock down prevents muscle formation, whereas HuR overexpression results in precocious differentiation. 40,41 Yet, it is highly likely HuR is interacting with many more targets inside these cells.…”
Section: Methodsmentioning
confidence: 99%
“…40,41 HuR siRNA knock down prevents muscle formation, whereas HuR overexpression results in precocious differentiation. 40,41 Yet, it is highly likely HuR is interacting with many more targets inside these cells. The exact explanations for this discrete phenotype are not presently understood.…”
Section: Methodsmentioning
confidence: 99%
“…HuR coordinately stabilizes messages for myogenin, MyoD and p21 during the myoblast to myocyte transition of C2C12 cells. 47,138 Artificial knockdown of HuR prevents myocyte differentiation of C2C12 myoblasts; 138 however, it should be noted that knockout mouse results indicate that the ARE-binding protein NF90 plays a major role in stabilizing muscle-specific transcripts. 92 In neurons, stabilization of transcripts such as p21 and GAP-43 by Hu proteins is linked to neuronal differentiation, neurite outgrowth and spatial learning.…”
Section: Coordinated Post-transcriptional Regulation In Differentiationmentioning
confidence: 99%